19‐5: Late‐News Paper: Characterization of carrier transport properties in working polymer light‐emitting diodes. Issue 1 (29th May 2019) - Takada, Makoto; Nagase, Takashi; Kobayashi, Takashi; Naito, Hiroyoshi
Abstract : Charge carrier transport properties of polymer semiconductors (electron and hole drift mobilities, localized‐tail‐state distributions, and bimolecular recombination constants) in working polymer light‐emitting diodes (PLEDs) are determined simultaneously using impedance spectroscopy (IS). The IS technique is also applicable to degradation analysis of the PLED.